2006
DOI: 10.1111/j.1530-0277.2006.00178.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Variations in Alcohol Dehydrogenase Genes With the Level of Response to Alcohol in Non‐Asians

Abstract: These findings suggest that studies searching for genes relating to the LR to alcohol as a vulnerability factor for AUDs should consider controlling for ADH1B genotype, as the ADH1B*2 allele could obscure the impact of other genetic polymorphisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 72 publications
4
38
0
3
Order By: Relevance
“…Although some studies have found that the ADH1B*2 allele is associated with a lower rate of alcohol dependence (Tanaka et al, 1996;Wall et al, 2005b;Whitfield, 1997), others have not (Luczak et al, 2004;Takeshita et al, 1994). Furthermore, some alcohol challenge studies have found significant associations between ADH1B and level of response to alcohol Duranceaux et al, 2006), but others have not (Heath et al, 1999;Peng et al, 2002). Thus, prior data do not consistently support the hypothesis that ADH1B*2 leads to decreased rates of alcohol dependence via a more intense response to alcohol, and any such relationship may be further obscured when level of response to alcohol is assessed using self-report.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have found that the ADH1B*2 allele is associated with a lower rate of alcohol dependence (Tanaka et al, 1996;Wall et al, 2005b;Whitfield, 1997), others have not (Luczak et al, 2004;Takeshita et al, 1994). Furthermore, some alcohol challenge studies have found significant associations between ADH1B and level of response to alcohol Duranceaux et al, 2006), but others have not (Heath et al, 1999;Peng et al, 2002). Thus, prior data do not consistently support the hypothesis that ADH1B*2 leads to decreased rates of alcohol dependence via a more intense response to alcohol, and any such relationship may be further obscured when level of response to alcohol is assessed using self-report.…”
Section: Discussionmentioning
confidence: 99%
“…With that, foetuses of mothers who carry the rare variant have a reduced exposure to alcohol compared to foetuses of mothers who carry the common variant. This negative association is very robust and has been replicated in numerous independent genetic studies (Reich et al, 1998;Whitfield et al, 1998;Saccone et al, 2000Saccone et al, , 2005Loew et al, 2003;Wall et al, 2005;Duranceaux et al, 2006;Luo et al, 2006;Zintzaras et al, 2006;Zhang et al, 2007;Ghosh et al, 2008;Tolstrup et al, 2008;Macgregor et al, 2009;Sherva et al, 2009;Zuccolo et al, 2009), confirming Assumption 3; we show the standard statistical tests below. This means that the potential exposure or treatment for child i whose mother does not carry the rare variant is at least as high as the potential treatment for the same child whose mother does carry the rare variant, for all i.…”
Section: Potential Outcomes Frameworkmentioning
confidence: 96%
“…Los efectos aversivos del etanol incluyen alteraciones fisiológicas periféricas como, molestias gastrointestinales (Adinoff, Iranmanesh, Veldhius y Fisher, 1998) y reacciones autonómicas (Duranceaux et al, 2006), así como efectos sobre el sistema nervioso central (SNC) (revisado en Pautassi et al, 2009).…”
Section: Propiedades Aversivas Del Etanolunclassified
“…Por último, cabe mencionar la existencia de diferencias, determinadas genética y/o ambientalmente, en la sensibi-lidad a los efectos aversivos del etanol, y éstas podrían, por tanto, influir sobre la probabilidad de búsqueda y consumo de etanol, como se extrae de diversas investigaciones realizadas con roedores (revisado en Broadbent et al, 2002;Escarabajal, 2003;y, Green y Grahame, 2008) y también con humanos (véase Duranceaux et al, 2006). En general, se ha observado que aquellos individuos que muestran mayores índices de CAG tienen una menor preferencia por el alcohol.…”
Section: Propiedades Aversivas Del Etanolunclassified
See 1 more Smart Citation